Optimizing Regency/City Government Public Information Openness Policy (Monev case study in Banten Province) - Hilman (Pengurus Pusat Perkumpulan Ilmuwan Administrasi Negara Indonesia (PIANI), 2024)
District / city governments as stated in law number 32 of 2014. One of the important things to understand is that the law states more explicitly the right of local governments to organize the affairs of government that fall under local authority. The Banten Provincial Government was encouraged by this authority to establish the Banten Provincial Information Commission and Regional Regulation No. 8 of 2012 concerning procedures for public information disclosure in the administration of local government from 2011-2015, 2015-2019 and 2019-2023. The research data collection method was taken from the results of the M&E activities of public agencies in 2023 for the category of district / city government in Banten province. The purpose of this M&E research is to identify tactics that can be used by district and city governments in Banten Province to transform into informed public bodies. The results of the M&E obtained that all district/city governments were categorized as INFORMATIVE public bodies with the highest score of 98.53 and the lowest score of 91.59. However, in the future, information and documentation management officials need to maximize the service of public information requests for applicants/users of information.